Z-Altman review: the case of beverage company in Latam - Lizarzaburu, Edmundo R. (2014)
Since 2000, the growth in beverage industry has been important. Overall, statistics show that Latam companies have presented a good financial performance. However, this performance could be highly questionable and, questions like what is going to happen in the next years in the industry or how likely a failure or bankruptcy could be experimented and needs to be answered. So, in order to answer such questions, an analysis is carried out by Ivan Vonne, a senior analyst. The method applied to this assessment is the Z-Score method developed by Altman in 1968. The literature review helped us to identify three types of Z-score, one developed by Edward Altman in 1968 called “Z-Score Model”, the other improved by Edward Altman in 1984 called “Company and Country Risk Models” for private companies and the last one improved by Altman, Hartzell y Peck in 1995 called “Emerging Market Scoring Model” (EMS Model) for non-manufactured companies and emerging market credits. The paper, focus in a Beverage Industry. One company, which has been chosen indiscriminately to evaluate the model, has been identified with operations in Peru and this company listed its equity in the Bolsa de valores de Lima (BVL, for its acronym in Spanish). In the first section you are going to find a brief introduction about the Company “Peruvian Beverage Inc.”. Second section develops the theory, its origins and the different ways it can be applied. Then, third section explains the way that the company performs in the industry, as well as the steps they follow to produce the final product. Fourth Section details how the operations have been carried out so far. Fifth section shows a brief analysis about the financial statements of the company. Sixth section assesses the Z-score model. Seventh and eighth sections establish why the model is not completely viable in Peru and an explanation about the results of sixth section. Finally, you can find references and the rest of the annexes in the last two sections.